Evidence that the second human pegivirus (HPgV-2) is primarily a lymphotropic virus and can replicate independent of HCV replication. Issue 1 (1st January 2020) - Wan, Zhengwei; Liu, Junwei; Hu, Fengyu; Shui, Jingwei; Li, Linghua; Wang, Haiying; Tang, Xiaoping; Hu, Chengguang; Liang, Yuanhao; Zhou, Yuanping; Cai, Weiping; Tang, Shixing
ABSTRACT: The second human pegivirus HPgV-2 is a novel blood-borne virus that is strongly associated with the hepatitis C virus (HCV) infection. However, the molecular evidence for their association as well as the natural history and tissue tropism of HPgV-2 remain to be elucidated. In this longitudinal study, a total of 753 patients including 512 HIV-1 and HCV co-infected patients were enrolled to characterize the natural history of HPgV-2 infection. Peripheral blood mononuclear cells (PBMCs) and liver biopsies were collected to determine the tissue tropism of HPgV-2 using immunohistochemical staining of the HPgV-2 antigen and in situ hybridization of HPgV-2 RNA. We documented both persistent HPgV-2 infection with the presence of HPgV-2 viral RNA and antibodies up to 4.6 years and resolved HPgV-2 infection, accompanied by a simultaneous decline of anti-HPgV-2 antibodies and clearance of HPgV-2 viremia. Furthermore, we observed the clearance of HCV, but not HPgV-2, by treatment with direct-acting antivirals (DAAs). Biochemical tests and pathological analyses did not reveal any indication of hepatic impairment caused by HPgV-2. HPgV-2 RNA and nonstructural antigen were detected in the lymphocytes, but not in the hepatocytes present in the liver biopsy samples. In addition, both positive- and negative-strand HPgV-2 RNAs were detected in PBMCs, especially in B cells. The present study is the first to provide evidence that HPgV-2 is a lymphotropic, but not a hepatotropic virus and that HPgV-2 replication is independent of HCV viremia. These new findings let us gain insights into the evolution and persistent infection of RNA viruses in humans.